The Philippine islands, 1493-1803 explorations by early navigators, descriptions of the islands and their peoples, their history and records of the Catholic missions, as related in contemporaneous books and manuscripts, showing the political, economic, commercial and religious conditions of those islands from their earliest relations with European nations to the beginning of the nineteenth century - Blair, Emma Helen 1911; Robertson, James Alexander 1873-1939; Bourne, Edward Gaylord 1860-1908 (A.H. Clark, 1903)
The present volume covers the period of 1583 to 1588 inclusive. At the close of two decades of Spanish occupation in the Philippines, the native population is decimated, and the Spanish colonists are poor, heavily burdened with taxation, and largely nonproducing. The islands are but nominally defended by a small, irregular, demoralized force of unpaid soldiers, whose lawlessness and arrogance render them dangerous to their own countrymen, and tyrants over the helpless natives. The Audiencia is a costly institution, a burden of which all the people complain. They have other grievances and many needs, which finally impel them to send a special envoy to Spain, to procure relief and aid from the home government.